Market liquidity and institutional trading during the 2007 - 8 financial crisis - Ser-Huang Poon; Michael Rockinger; Konstantinos Stathopoulos (The University of Manchester, Manchester Business School, 2011)
During the financial crisis in 2007-8, the quoted spread for the average S&P 1500 firm increased by 50%, while the systematic liquidity risk increased by 34%. We find that the trading of a firm's equity by institutional investors increased the firms' quoted spreads, and led to a higher liquidity commonality during the crisis. Institutional sell-side herding contributed strongly to both effects. Our results are robust to different specifications and consistent with theoretical and anecdotal evidence regarding the role of herding during a crisis.
Keywords: G01; G14; G20; 330; Institutional Herding; Institutional Count; Institutional Holdings; Market Liquidity; Financial Crises; Betriebliche Liquidität; Marktliquidität; Institutioneller Investor; Herdenverhalten